2018
DOI: 10.5455/apd.273231
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anger control, suicide behavior and attention deficit hyperactivity disorder among outpatients with cannabis use

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This finding is correlated with the previous study where it was found that the prevalence rate of depression is higher in single diabetic patients. [ 15 ] They found that marriage integrates people into wider social networks, buffers life from strains, and provides personal security, meaningfulness, and purpose.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is correlated with the previous study where it was found that the prevalence rate of depression is higher in single diabetic patients. [ 15 ] They found that marriage integrates people into wider social networks, buffers life from strains, and provides personal security, meaningfulness, and purpose.…”
Section: Discussionmentioning
confidence: 99%